THE ANALYSIS OF THE ENVIRONMENTAL IMPACT AND COMMUNITY ECONOMIC SOCIAL CHANGE THAT WAS INCURRED BY THE BEACH RECLAMATION VIEWED FROM AN ISLAMIC PERSPECTIVE (CASE STUDY OF KENJERAN BEACH SURABAYA) - Putri Amalia Zahrah; Sri Herianingrum (Universitas Airlangga, 2020)
This study aims to determine how the environmental impacts arising from the beach reclamation activities in the Kenjeran Beach, Surabaya, viewed from the Islamic perspective. The method used is descriptive qualitative case study method where this research was conducted by conducting interviews, documentation and direct observation. The object of this research is the Kenjeran Beach in Surabaya, where the data were obtained based on interviews conducted with ten informants consisting of the government apparatus of the Bulak and Kenjeran Districts, traders, and the surrounding community. Based on the results of the study showed that the infrastructure development carried out caused changes in the ecosystem. The environmental impact also affects the socio-economic life of the surrounding community. Kenjeran Beach Reclamation Activity has not fully met Al-Istishlah indicators in environmental care. And in several aspects of the Islamic Maqashid indicators also have not been run optimally.Keywords: environmental impact, socio-economic change, beach reclamation, kenjeran beach, Islamic perspective.REFFERENCE Al-Qur’an Creswell, John W. (2010). Research design pendekatan kualitatif, kuantitatif, dan mixed. Yogyakarta: Pustaka PelajarDahuri, R. 2001. Pengelolaan sumberdaya wilayah pesisir dan lautan secara terpadu. Jakarta: PT. Pradnya Paramita. Habibi, A. (2012). Trade off kerusakan sumber daya alam dan pembangunan ekonomi. Asas: Jurnal Hukum Ekonomi Syariah, 4(1), 1-5. Herianingrum, Sri. (2014). Implementation of maqashid al sharia as a model of economic development agriculture in East Java. Journal of Business and Economic, 5(9), 1701-1708.Meirison. (2017). Jenis kepemilikan dalam sistem ekonomi Islam. Maqdis: Jurnal Kajian Ekonomi Islam, 2(1), 93-109.Moleong, Lexy J. (2007). Metode penelitian kualitatif. Bandung: PT Remaja PosdakaryaN.d. (2013). Rencana tata ruang wilayah kota Surabaya. Surabaya: Pemerintah Kota Surabaya.Otto Soemarwoto. (2004). Ekologi, lingkungan hidup dan pembangunan. Jakarta: Djambatan.Sugiyono. (2016). Metode penelitian kuantitatif kualitatif dan R & D. Bandung: Alfabeta.Yakin, Adinul. (2015). Ekonomi sumber daya alam dan lingkungan: teori, kebijakan, dan aplikasi bagi pembangunan berkelanjutan. Jakarta: Akademika Pressindo.Peraturan Menteri Negara Lingkungan Hidup No. 05 Tahun 2012 tentang Jenis Rencana Usaha dan/atau Kegiatan yang Wajib meiliki analisis mengenai dampak lingkungan Hidup (AMDAL)Peraturan Menteri Perhubungan No PM 52 Tahun 2011PP Nomor 27 Tahun 1999, tentang Analisis Mengenai Dampak Lingkungan (AMDAL) PP Nomor 27 Tahun 2012 tentang Izin Lingkungan RTRW Surabaya, 2013UU Nomor 27 Tahun 2007, tentang Pengelolaan Wilayah Pesisir Dan Pulau-Pulau Kecil.UU Nomor 23 Tahun 1997 tentang Pengelolaan Lingkungan Hidup.